Innovation Primary Care Physician in the Era of JKN in Building Interpersonal Communication With Patients (Case Study of Primary Care Physicians In Surakarta to Universal Health Coverage) - Nurfitri Kurniawati, Prahastiwi Utari & Sudarmo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study entitled the innovation of primary care physicians in the era of JKN inbuilding interpersonal communication with patients (Case study of primary carephysician at Surakarta in universal health). This study aims to provide learning andknowledge development within the health care industry with the application ofeducational symbiosis innovation. This research uses case study method, that isqualitative data analysis method that emphasizes on certain cases that happened inthe object of current analysis. This method uses descriptive analysis with inductiveapproach in analyzing data. WHO has agreed on achieving universal healthcoverage (UHC) in 2014. Universal health coverage is a health system that ensuresevery citizen in the population has fair access to high quality promotive,preventive, curative and rehabilitative services at an affordable cost. Universalcoverage contains two core elements: access to fair and quality health services forevery citizen, and the protection of financial risk when citizens use health services.In Indonesia UHC system is implemented in 2019.The subjects of the study were primary care physicians and their patients residingin Surakarta City. The results show that the interpersonal relationships of primarycare physicians with their patients can be well established and effective in the eraof universal health. Innovate the service industry by providing patient-centeredknowledge. The centralized patient communication theory (PCM), which is part ofthe relationship communication theory, provides an overall explanation of thepatient-centered interpersonal communication process. Helps to change the stressorin the patient's self into a healthy lifestyle.Keywords: interpersonal communication, primary care physician , innovation.